Maternal employment characteristics as a structural social determinant of breastfeeding after return to work in the European Region: a scoping review - Pauline Brugaillères; Séverine Deguen; Sandrine Lioret; Sahar Haidar; Corinne Delamaire; Emilie Counil; Stéphanie Vandentorren (BMC, 2024)
Abstract Background The European Region has the lowest rate of exclusive breastfeeding at 6 months worldwide. Improving work-related breastfeeding issues is important given that women may have difficulties combining work and breastfeeding, especially those in precarious working situations, which adds to their adversity. This scoping review overviews research on the maternal employment characteristics that support breastfeeding continuation after return to work in the European Region. Methods Studies published from 2013 to 2023 were collected from Scopus, PubMed, and PsycInfo. Quantitative and qualitative studies published in English or French that explored the association between maternal employment characteristics and any breastfeeding status, duration, or experience were included. Participants included were mothers of healthy children who continued breastfeeding after resuming work. The main determinants were work-related factors that can lead to socially differentiated working conditions, including type of employment (e.g., occupation, employed/self-employed status, type of contract, working time, occupational prestige), working conditions (e.g., work schedule, decision latitude, latitude to organize worktime), and work environment (e.g., occupational exposure, family-friendly workplace policy, social support). The geographic area encompassed countries included in the World Health Organization European Region. Results Of the 693 single studies retrieved and screened, 13 were included in the review. Eight studies focused on combining work and breastfeeding, while the others had a broader spectrum by investigating breastfeeding determinants. The represented countries were Spain (n = 4), France (n = 4), UK (n = 2), Ireland (n = 2), and the Netherlands (n = 1). Results highlighted the heterogeneity of measures, time frames, and fields of inquiry, thus revealing a lack of conceptual framework regarding the links between work, breastfeeding, and social health inequalities. Nonetheless, being self-employed, working in a non-manual profession with time flexibility, having lactation rooms at work, being supported by co-workers, and having a breastfeeding workplace policy were salient factors that supported breastfeeding in working mothers. Conclusions Supporting working mothers who choose to breastfeed is important given the myriad of adverse factors faced by mothers and their children. These results advocate for targeted actions at the workplace such as time flexibility, breastfeeding facilities, and the promotion of breastfeeding-friendly policies.